AcnSP – A Novel Small Protein Regulator of Aconitase Activity in the Cyanobacterium Synechocystis sp. PCC 6803 - de Alvarenga, Luna V.; Hess, Wolfgang R.; Hagemann, Martin (Frontiers in Microbiology, 2020)
Synechocystis sp. PCC 6803 is a widely used model cyanobacterium whose genome has been well annotated. However, several additional small protein coding sequences (sORFs) have been recently identified, which might play important roles, for example in the regulation of cellular metabolism. Here, we analyzed the function of a sORF encoding a 44 amino acid peptide showing high similarity to the N-terminal part of aconitase (AcnB). The expression of the gene, which probably originated from a partial gene duplication of chromosomal acnB into the plasmid pSYSA, was verified and it was designated as acnSP. The protein-coding part of acnSP was inactivated by interposon mutagenesis. The obtained mutant displayed slower growth under photoautotrophic conditions with light exceeding 100 µmol photons m-2 s-1 and showed significant changes in the metabolome compared to wild type, including alterations in many metabolites associated to the tricarboxylic acid (TCA) cycle. To analyze a possible direct impact of AcnSP on aconitase, the recombinant Synechocystis enzyme was generated and biochemically characterized. Biochemical analysis revealed that addition of equimolar amounts of AcnSP resulted in an improved substrate affinity (lower Km) and lowered Vmax of aconitase. These results imply that AcnSP can regulate aconitase activity, thereby impacting the carbon flow into the oxidative branch of the cyanobacterial TCA cycle, which is mainly responsible for the synthesis of carbon skeletons needed for ammonia assimilation.